2021
DOI: 10.1186/s12937-021-00676-7
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status five years after the adjustment of universal salt iodization: a cross-sectional study in Fujian Province, China

Abstract: Background Universal salt iodization program was introduced to China to eliminate iodine deficiency disorders in 1995. In 2012, Fujian Province decreased the concentration of iodized table salt according to the national unified requirement. This study aimed to assess the effect on iodine status after the adjustment, providing evidence for further adjustment in Fujian Province. Methods Sampling units were selected by multistage cluster sampling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
7
10
0
1
Order By: Relevance
“…In Guangzhou, the coverage rate of iodized salt was 96.00% of the total population. This result was similar to that obtained in Fujian Province (95.1%), a coastal area near Guangzhou in China [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In Guangzhou, the coverage rate of iodized salt was 96.00% of the total population. This result was similar to that obtained in Fujian Province (95.1%), a coastal area near Guangzhou in China [18].…”
Section: Discussionsupporting
confidence: 90%
“…In Guangzhou, the coverage rate of iodized salt was 96.00% of the total population. This result was similar to that obtained in Fujian Province (95.1%), a coastal area near Guangzhou in China ( 18 ). Interestingly, we found that the coverage rate of iodized salt was significantly higher in rural residents, although they had a much lower median UIC than urban residents.…”
Section: Discussionsupporting
confidence: 90%
“…At the time of the 2011 National Iodine Deficiency Disorder survey, 95.3% of households were consuming salt with 20–50 ppm of iodine (the Chinese national standard) [ 27 ]. However, we also noticed a rebound in the incidence rates of iodine deficiency among the female elderly in China from 2004 to 2017, which might be related to the adjustment of decreasing the concentration of iodized table salt in some provinces in recent years [ 28 ]. Moreover, due to changes health consciousness, there was a reduction in salt consumption, especially among women [ 29 ], which might have also resulted in a decline in iodine intake.…”
Section: Discussionmentioning
confidence: 99%
“…Mild iodine deficiencies have been reported in most European countries as well as the United States (24,25). Similarly, iodine deficiencies have been widely reported in many regions of China since the implementation of the revised USI standards (15,16,(26)(27)(28)(29)(30). Severe iodine deficiency (UIC lower than 50 µg/L) during pregnancy is associated with maternal and fetal thyroid dysfunction and destructive consequences on fetal intrauterine growth and neurological and cognitive development that can result in miscarriage, stillbirth, and infant mortality (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%